2007
DOI: 10.1097/ico.0b013e3180de4953
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant Beauveria bassiana Keratitis

Abstract: B. bassiana is a rare cause of keratitis that may show significant resistance to topical and systemic antifungals but was treated successfully with the addition of oral posaconazole to topical voriconazole. Confocal microscopy and corneal smears may be of benefit in identifying and directing therapy for this slow-growing fungus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 11 publications
4
8
0
Order By: Relevance
“…The course of our non-necrotic keratitis case was slow-growing, there was no clinical improvement after treatment with voriconazole even though voriconazole was the preferable antibiotic according to the sensitivity tests. The cases of B. bassiana reported by Low et al , Kisla et al , and Tu et al , were also slow-growing with late penetration into the corneal stroma which is consistent with our case [ 6 , 7 , 12 ]. In addition, the resistance to antifungal therapy was also consistent with our case [ 6 8 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…The course of our non-necrotic keratitis case was slow-growing, there was no clinical improvement after treatment with voriconazole even though voriconazole was the preferable antibiotic according to the sensitivity tests. The cases of B. bassiana reported by Low et al , Kisla et al , and Tu et al , were also slow-growing with late penetration into the corneal stroma which is consistent with our case [ 6 , 7 , 12 ]. In addition, the resistance to antifungal therapy was also consistent with our case [ 6 8 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…The in vivo response shows a stabilization of the corneal lesion, allowing amphotericin B to inhibit worsening of the disease as seen in previous reports 22.…”
Section: Case Reportsupporting
confidence: 77%
“…8 Its efficacy on Paecilomyces lilacinus has recently been shown in a murine infection model. 10 In addition, it has recently been used in a case with refractory keratitis due to Beauvaria bassiana , as reported by Tu et al 11 Further, Sponsel et al successfully treated a case of Fusarium keratitis, where posaconazole was used both orally and topically. 12 However, the commercial preparation of posaconazole available now is an oral suspension and should not be used topically as it contains various additives, including dyes.…”
Section: Discussionmentioning
confidence: 97%
“…Tu et al reported that posaconazole had to be discontinued after one month of therapy due to the development of elevated liver function tests and pleural effusion. 11 …”
Section: Discussionmentioning
confidence: 99%